Peningkatan Kualitas Adab Santri Melalui Penyuluhan Kitab Mitra Sejati di Madrasah Diniyah Al-Bukhori - Suryanti, Ria Finola Alfani Sari; Riditiya Nurhidayati; Yuanita Septiana Sari; Verbena Ayuningsih Purbasari (Institut Agama Islam Negeri Ponorogo, 2023)
Abstract: Madrasah Diniyah (MADIN) or Islamic Educational Institution Al-Bukhori is a non-formal institution located in the village of Ngloning, Slahung, Ponorogo. During the learning process, the researcher observed students who were still noisy, not paying attention to the teacher's explanations, and lacking in manners. In response to this, the researcher endeavored to conduct counseling using the Mitra Sejati book to improve the behavior of students at MADIN Al-Bukhori. The objective of this research is to enhance the students' conduct at MADIN Al-Bukhori. The method employed in this study is the ABCD approach with the principle of Everyone Has Potential (Nobody Has Nothing) and using appreciative inquiry techniques. The research results indicate that the implementation of the Mitra Sejati book has led to an improvement in the students' behavior. Students are more inclined to pay attention to the teacher's explanations, and in their interactions with both the teacher and their peers, they apply good manners and etiquette.